2022
DOI: 10.3389/fcell.2022.892315
|View full text |Cite
|
Sign up to set email alerts
|

Sex-differential RXRα gene methylation effects on mRNA and protein expression in umbilical cord of the offspring rat exposed to maternal obesity

Abstract: Maternal obesity (MO) induces negative consequences in the offspring development. Adiposity phenotype is associated with maternal diet at early pregnancy and DNA methylation marks in the RXRα promotor at birth. Glucocorticoids play an important role in the regulation of metabolism through the activation of nuclear hormone receptors such as the RXRα protein. The aim of the study was to analyze steroid hormone changes at the end of pregnancy in the obese mother and RXRα gene methylation in the umbilical cord. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…provide an extensive review of these dysregulations, highlighting the complex endocrine environment in obese pregnancies and its potential implications for both maternal and fetal health ( 154 ). One study in rodents demonstrated that maternal obesity resulted in low fetal weight in the F1 generation, accompanied by modified DNA methylation and altered expression of the nuclear hormone receptor RXRα in a sex-dependent manner ( 155 ). Methylation of RXRα has also been linked to childhood adiposity ( 137 ).…”
Section: Maternal Inheritancementioning
confidence: 99%
“…provide an extensive review of these dysregulations, highlighting the complex endocrine environment in obese pregnancies and its potential implications for both maternal and fetal health ( 154 ). One study in rodents demonstrated that maternal obesity resulted in low fetal weight in the F1 generation, accompanied by modified DNA methylation and altered expression of the nuclear hormone receptor RXRα in a sex-dependent manner ( 155 ). Methylation of RXRα has also been linked to childhood adiposity ( 137 ).…”
Section: Maternal Inheritancementioning
confidence: 99%
“…Human and controlled animal studies have shown that maternal obesity has detrimental lifelong consequences on offspring by programming their cells, tissues, and organs, as well as their structures and functions. Maternal obesity programs offspring metabolic disorders through several mechanisms, including metabolic, hormonal [ 4 , 5 , 6 , 7 ], and epigenetic changes [ 8 , 9 ], as well as through oxidative stress [ 10 , 11 ], a commonly proposed mechanism for liver injury and the progression of age-related diseases [ 10 ]. Non-alcoholic fatty liver disease (NAFLD) is the most prevalent form of liver disorder and is considered a global epidemic.…”
Section: Introductionmentioning
confidence: 99%